The reign of Henry IV : rebellion and survival, 1403-1413 - Dodd, Gwilym; Biggs, Douglas, 1960- (York Medieval Press ; in association with Boydell Press, 2008)
Groundbreaking new essays provide a wealth of insight into a less-explored period of Henry's reign.